4(3m-4)=3(m+9)+2

Simple and best practice solution for 4(3m-4)=3(m+9)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3m-4)=3(m+9)+2 equation:



4(3m-4)=3(m+9)+2
We move all terms to the left:
4(3m-4)-(3(m+9)+2)=0
We multiply parentheses
12m-(3(m+9)+2)-16=0
We calculate terms in parentheses: -(3(m+9)+2), so:
3(m+9)+2
We multiply parentheses
3m+27+2
We add all the numbers together, and all the variables
3m+29
Back to the equation:
-(3m+29)
We get rid of parentheses
12m-3m-29-16=0
We add all the numbers together, and all the variables
9m-45=0
We move all terms containing m to the left, all other terms to the right
9m=45
m=45/9
m=5

See similar equations:

| | | 18t=27 | | 13x+6-7x=42 | | 2.5n+10=n+1.5n-7 | | 52+6y=64 | | 2x=112-X=5X-8=180 | | w/5+4=6 | | −5x−4(4−2x)=4x−8 | | -98=-4(-3+5x)-2x | | 14x+18=36 | | 3x^2-1=48 | | -4b+6b=-34+20 | | 3b+3b=15 | | 5(2x-1)-6(x+1)=1 | | -5x-16=8x+3 | | 4x+65=180 | | 5(2xx1)=25 | | 4m+7=10m-11 | | 4-4n=43 | | 5x-(14-x)=-13-2x | | 4r+6r=20 | | 7+3y-2=8y+8-4y | | 3/4x-2=52 | | -3(x+7)=7x+49 | | 6(n+7=4+5(2n+6) | | 10+8r=4+7(r+2) | | 4k-6k=-12 | | 3b+9=9 | | 6x+3=-3+4x+10 | | 19.17-6.35-16.3r=-19.03-19.8r | | 16-4u=-16 | | 9={1}{4}(6x+12) |

Equations solver categories